Effect of silicon on rice blast disease - Mohammad Hailmi, Sajili (2012)
Silicon is the second most plentiful element in soil and is beneficial for a large variety of plants. It is concentrated in plant tissues in quantities similar to that of macronutrients. Considerable damages to plants caused by abiotic stresses such as drought stress, salinity stress, heavy metal stress and nutrient imbalance, as well as biotic stresses like insect pests and pathogens and even herbivorous atView tacks, have been reported to be reduced significantly by silicon application. Among rice diseases, blast is recognized as the most devastating one. Silicon fertilization has been reported to be efficacious in controlling and mitigating rice blast severity. Two different hypotheses are proposed for the ability of silicon to lessen disease severity. The first hypothesis emphasizes on silicon function as a mechanical barrier against appressorial penetration, while the second hypothesis is based upon the belief that silicon has some physiological roles in disease resistance. © Universiti Putra Malaysia Press.